ANEKA DISRUPSI PEMBELAJARAN BAHASA ARAB DI PONDOK PESANTREN - Azisi, Azisi; Badri, Badri (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
Islamic boarding schools, as traditional Islamic educational institutions in Indonesia, play a central role in preserving and promoting Islamic religious and cultural traditions. One of the important elements of education in Islamic boarding schools is the teaching of Arabic. Arabic is not only a means of understanding the teachings of Islam but also a gateway to the rich intellectual heritage of the Islamic world. This qualitative research uses open questionnaires as a data collection technique. The questionnaires were distributed to Arabic teachers in seven Islamic boarding schools in Situbondo. The results cite the strengths of Islamic boarding schools in the form of their long-standing tradition of teaching Arabic and Islamic culture, the presence of knowledgeable teachers, a focus on memorizing the Quran, and a communal learning environment. However, weaknesses in the traditional curriculum may overlook practical aspects such as the use of digital technology in Arabic language learning in the modern world. To improve Arabic language learning in Islamic boarding schools, it is important to address the practical aspects of the language, maximize opportunities for collaboration and adoption of technology, and address challenges such as cultural and social change and competition from formal educational institutions offering Arabic language instruction.